MAPPING RESEARCH WASTE FILTER CIGARETTE BUTTS AS A SUBSTITUTE FOR COARSE AGGREGATE IN CONCRETE BY THE METHOD OF SYSTEMATIC LITERATURE REVIEW - Thofan Agung Wibowo; Anisah Anisah; M. Agphin Ramadhan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2021)
This study aims to determine the mapping of research related to cigarette butts filter waste as coarse aggregate for making concrete according to its category. This study uses systematic literature review techniques to conduct research by analyzing the literature. Literature collection is done by searching several digital libraries by entering a search string that has been made based on the research queation with publication limits between 2011-2020. The results showed that from 182 literature obtained 4 of them were suitable for analysis. Based on the 4 literatures, it is known that normal concrete and lightweight concrete are produced from cigarette butts filter waste. The concrete that is most often made is normal concrete and the best compressive strength value that can be produced is 29.6 MPa with a cigarette butt filter waste mixture of 0.1% of the concrete density. The best quality produced is medium quality with K 300.84 and is included in the category of structural concrete.